THE ROLE OF BUMDES IN INCREASING VILLAGE ORIGINAL INCOME IN KANRUNG VILLAGE - JAYADI, MUHAMMAD FAJRUL; Zulkifli; Salim, Emil Salim; Akram, Muh. (Program Studi Administrasi Publik, 2024)
The goal of BUMDes is to increase the village's original income to plan and manage the village economy. this research is to analyze the role of BUMDes in increasing PADes in Kanrung Village. In addition, the purpose of establishing BUMDes is to serve rural communities in developing productive economic businesses, as well as providing various business media to reduce and increase people's welfare. indicators include business results, Asset Results, Self-Help, and other Village original income. To find out the role of BUMDes in increasing village original income research includes reviewing the literature by looking for theoretical references that are relevant to the cases or problems found. There are several supporting and inhibiting factors that need attention. Supporting factors include government support, community participation, availability of local resources, and adequate skills and knowledge. While the inhibiting factors include limited capital, lack of skills and knowledge, competition with other businesses, and lack of public awareness and interest.